Fluvastatin Inhibits Basal and Stimulated Plasminogen Activator Inhibitor 1, but Induces Tissue Type Plasminogen Activator in Cultured Human Endothelial Cells - Mussoni, Luciana; Banfi, Cristina; Sironi, Luigi; Arpaia, Magda; Tremoli, Elena (Thrombosis and Haemostasis, 2000)
The effects of fluvastatin, a synthetic hydroxymethylglutaryl coenzyme A (HMG-CoA) inhibitor, on the biosynthesis of tissue plasminogen activator (t-PA) and of its major physiological inhibitor (plasminogen activator inhibitor type 1, PAI-1) were investigated in cultured human umbilical vein endothelial cells (HUVEC). Fluvastatin (0.1 to 2.5 µM), concentration-dependently reduced the release of PAI-1 antigen by unstimulated HUVEC, subsequent to a reduction in PAI-1 steady-state mRNA levels and de novo protein synthesis. In contrast, it increased t-PA secretion.The drug also reduced PAI-1 antigen secreted in response to 10 µg/ml bacterial lipopolysaccharide (LPS), 100 U/ml tumour necrosis factor α (TNFα) or 0.1 µM phorbol myristate acetate (PMA).Mevalonate (100 µM), a precursor of isoprenoids, added to cells simultaneously with fluvastatin, suppressed the effect of the drug on PAI-1 both in unstimulated and stimulated cells as well as on t-PA antigen. Among intermediates of the isoprenoid pathway, all-trans-geranylgeraniol (5 µM) but not farnesol (10 µM) prevented the effect of 2.5 µM fluvastatin on PAI-1 antigen, which suggests that the former intermediate of the isoprenoid synthesis is responsible for the observed effects.
Keywords: Plasminogen activator; endothelial cells; 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor; isoprenoids